Cities and affordable housing planning, design and policy nexus - Tsenkova, S. (Routledge Taylor & Francis Group, 2022)
"This book provides a comparative perspective on housing and planning policies affecting the future of cities, focusing on people-based and place-based outcomes using the nexus of planning, design and policy. A rich mosaic of case studies features good practices of city-led strategies for affordable housing provision, as well as individual projects capitalising on partnerships to build mixed-income housing and revitalise neighbourhoods. Twenty chapters provide unique perspectives on diversity of approaches in seven countries and fifteen cities in Europe, Canada and the USA. Combining academic rigour with knowledge from critical practice, the book uses robust empirical analysis and evidence-based case study research to illustrate the potential of affordable housing partnerships for mixed-income, socially inclusive neighbourhoods as a model to rebuild cities. Cities and Affordable Housing is an essential interdisciplinary collection on planning and design that will be of great interest to scholars, urban professionals, architects, planners and policy-makers interested in housing, urban planning and city building"--